Isolation and partial purification of a hemolytic sphingomyelin-inhibitable fraction from the sea anemone Anthopleura nigrescens - Alvarado Mesén, Javier (2014)
Actinoporins are highly hemolytic pore-forming proteins with a molecular mass of around 20 kDa and high affinity for sphingomyelin-containing membranes. On the crude extract of the sea anemone Anthopleura nigrescens, the hemolytic activity (HA) was detected. In order to identify the presence of pore-forming proteins similar to actinoporins in this anemone, the fractionation and analysis of its crude extract was carried out. The aqueous extract of the whole body was subjected to gel filtration chromatography on Sephadex G50 medium rendering three resolved peaks (P-I, P-II, and P-III) as measured by their absorbance at 280 nm. Functional characterization of the crude extract and chromatographic fractions was evaluated by HA against human red blood cells. The crude extract and two peaks (P-II and P-III) showed HA. Interestingly, the HA of the crude extract and P-II were specifically inhibited by small unilamellar vesicles of phosphatidylcholine: sphingomyelin (1:1). Both the crude extract and P-II revealed the existence of at least one protein band around 20 kDa by SDS-PAGE. The inhibition by sphingomyelin of the whole body extract HA and the localization of this property in P-II that could be associated with a protein of around 20 kDa suggest the presence of at least one novel actinoporin in A. nigrescens. Furthermore, this is the first report of a biochemical activity for this sea anemone. Work is in progress in order to purify and characterize the molecular entities responsible for this HA inhibited by sphingomyelin.